Conjectura da curvatura escalar normal - Fonseca, Aurineide Castro (2008)
In this work we present a proof of the Normal Scalar Curvature Conjecture for submanifolds Mn, isometrically immersed into space forms Nn+m(c) of constant sectional curvature c.